Chronic bronchitis leads to accelerated hyperinflation in COPD patients during exercise. Issue 4 (19th March 2015) - Zhang, Wen; Lu, Haitao; Peng, Liyue; Ren, Xiaoxia; Lu, Yong; An, Li; Zhang, Hong; Tan, Xiaoyue; Sun, Xingguo; Huang, Kewu
Abstract Background and objective It is not known whether patients with chronic obstructive pulmonary disease (COPD) have a different exercise capacity with (CB+) or without accompanying chronic bronchitis (CB−). Methods We conducted spirometry, a 6‐min walk distance test and cardiopulmonary exercise test in 50 age‐matched healthy control subjects, 45 COPD patients without CB (CB−) and 37 COPD patients with CB (CB+). A multiple regression model was established to identify factors independently associated with peak oxygen consumption (<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgjj8w5bm9" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />V˙O2</alternatives>). Results Patients with and without CB had similar forced expiratory volume in 1 s (FEV1). CB+ patients had a lower <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgjj8w5bks" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />V˙O2</alternatives>. CB+ and CB− participants had similar increases in tidal volume at peak exercise; however, CB+ patients had an increased respiratory rate (RR). These patients reached the peak value for ratio of end‐expiratory lung volume to total lung capacity (TLC) at a lower work load. A stepwise multiple linear regression analysis identified chronic bronchitis, FEV1, diffusing capacity for carbon monoxide, the ratio of residual volume to TLC and serum tumour necrosis factor‐α as independent predictors of peak <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgjj8w5bnt" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />V˙O2</alternatives>. Conclusions CB significantly lowers exercise capacity in COPD patients because of dynamic hyperinflation during exercise. The accelerated dynamic hyperinflation may contribute to increased airway and systemic inflammation in COPD patients.